Development and marketing of Ilocos empanada a technical feasibility - Dela Cruz, Marissa Raymundo; Francisco, Ma. Leonora dL. (2004., 2004)
ABSTRACT A study was performed to develop and market Ilocos empanada in Metro Manila. The study surveyed the rice variety to be used in the preparation for the empanada crust. A consumers acceptance test was also conducted to campare the formulated product with that of a reference empanada, the Ilocos empanada sold along Katipuan Avenue, Queazon City. Results showed that between rice variety IR 42 and glutinous rice, the former variety was found to be more acceptable in terms of texture, integrity and price. On the consumers test conducted, the formulated empanada was found to be significantly different with that of the reference empanada in terms of overall acceptability, color of the dough, tenderness and moistness of the filling, aroma and plumpness of the empanada, and crispiness of the crust. Cost analysis showed that one empanada costs Php 16.82. The product however can be sold at Php 30.00 per price, considering that the reference empanada is being sold at Php 35.00 per piece.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Snack foods